2010
DOI: 10.1007/s10267-009-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and evolution of subsection Magnicellulatae (Erysiphaceae: Podosphaera) with special reference to host plants

Abstract: The subsection Magnicellulatae of the genus Podosphaera section Sphaerotheca belongs to the tribe Cystotheceae of the Erysiphaceae, which has the characteristic of producing catenate conidia with distinct fibrosin bodies. In this study, we newly determined the nucleotide sequences of the D1/D2 domains of the 28S rDNA region and the sequences of the rDNA internal transcribed spacer (ITS) region to investigate the relationships between the phylogeny of this fungal group and their host plants. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In fact, some of the morphologically similar mitosporic powdery mildew species do not differ in their ITS sequences in more than one to a few nucleotides (e.g., Kiss et al 2005Kiss et al , 2008Cook et al 2006) and the same degree of variation was found among powdery mildews infecting different host plant species/genera and belonging to as yet unresolved species complexes (e.g., Matsuda and Takamatsu 2003;Kiss et al 2006;Takamatsu et al 2008;Ito and Takamatsu 2010). Therefore, the accurate determination of the ITS sequences is essential for a precise identification of powdery mildew fungi, especially if morphological and/or host range data are limited.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, some of the morphologically similar mitosporic powdery mildew species do not differ in their ITS sequences in more than one to a few nucleotides (e.g., Kiss et al 2005Kiss et al , 2008Cook et al 2006) and the same degree of variation was found among powdery mildews infecting different host plant species/genera and belonging to as yet unresolved species complexes (e.g., Matsuda and Takamatsu 2003;Kiss et al 2006;Takamatsu et al 2008;Ito and Takamatsu 2010). Therefore, the accurate determination of the ITS sequences is essential for a precise identification of powdery mildew fungi, especially if morphological and/or host range data are limited.…”
Section: Introductionmentioning
confidence: 97%
“…These sequences were always identical or 98-99% similar within, but always differed among, all the well-defined powdery mildew species and formae speciales identified based on morphological and/or host range criteria (e.g., Cook et al 2006;Inuma et al 2007;Kiss et al 2008;Shiroya and Takamatsu 2009;Takamatsu et al 2009;Heluta et al 2009). Phylogenetic relationships among various powdery mildew species have also been elucidated mainly based on ITS, and 28S and 18S, nrDNA sequences (e.g., Matsuda and Takamatsu 2003;Cunnington et al 2005;Kiss et al 2006;Takamatsu et al 2008Takamatsu et al , 2009Ito and Takamatsu 2010). Comprehensive phylogenetic analyses based on DNA sequences other than nrDNA have only been carried out in the genus Blumeria infecting monocots (Inuma et al 2007) and in the grapevine powdery mildew pathogen, Erysiphe necator (Brewer and Milgroom 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive phylogenetic analyses of these groups might reveal a host expansion strategy of the Erysiphaceae to herbaceous plants. To resolve the postulated strategy, we conducted molecular phylogenetic analyses of herb-parasitic groups of the Erysiphaceae (Hirata et al 2000;Takamatsu et al 2000Takamatsu et al , 2006Takamatsu et al , 2009Khodaparast et al 2001Khodaparast et al , 2007Matsuda and Takamatsu 2003;Inuma et al 2007;Heluta et al 2010;Ito and Takamatsu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of regional monographs and checklists have been published. But, above all, the introduction of molecular methods in the taxonomy of the Erysiphales provided better insight into the phylogenetic context and structure of this fungal group and led to significant changes in the circumscriptions of the genera concerned (e.g., Saenz and Taylor 1999;Takamatsu et al 1999Takamatsu et al , 2000Takamatsu et al , 2008Takamatsu et al , 2010Mori et al 2000;Takamatsu 2004;Matsuda and Takamatsu 2003;Hirose et al 2005;Ito and Takamatsu 2010). The whole structure of the family Erysiphaceae has been altered and adapted in order to reflect the new anamorphic and phylogenetic knowledge.…”
mentioning
confidence: 97%